Molecular genetic factors influencing outcomes of Helicobacter pylori infection at Khakasia republic inhabitants - Ye. S. Ageyeva; O. V. Shtygasheva; N. V. Ryazantseva; V. V. Tsukanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
Aim of investigation. To detect molecular-genetic features of Helicobacter pylori and polymorphism of main immunoregulatory interleukins genes at Khakases, to estimate their effect on outcomes of infection pathogen.Material and methods. Investigation was carried out at native population of Khakasia with H. pyloriassociated diseases: peptic ulcer and chronic gastritis. Prevalence of interleukins IL1β, IL1Ra, IL8 and CYP2C19 gene polymorphism was studied by restriction analysis, VacA +– and CagA +– subtypes of H. pylori – by polymerase chain reaction.Results. Peptic ulcer was associated to S1S2 Vac A subtypes at Caucasians, while at Khakases – to Cag А strains of H. pylori. Interrelation between CagA, АА251 ILs – 8 and the risk of peptic ulcer development was revealed at Khakases (OR=3,1, 95% CI 1,1–8,8). Most common variants among Khakases were – СС +3953 IL1 β (84%) and R4/R4 IL1Ra (76%), with not high expression level. Frequent genotype wt/wt +681 CYP2C19 (89,3%) was associated to the risk of peptic ulcer development (OR=4,17, 95% CI 1,04–19,39).Conclusions. Population-based genetic determinants (СС +3954 IL1β, R4/R4 IL1Ra), that establish higher protection level from H. pylori-associated diseases at Khakases, than at Caucasians were revealed. Risk factors for peptic ulcer at Khakases include carriage of CagA H. pylori strain, АА-251 of IL8 gene, GG +681 of CYP2C19 gene.